A method for testing the adhesion firmness of white cardboard box pasting
By using the test method of cutting test samples, molds with rectangular holes and water-based adhesives in the adhesive firmness detection of white cardboard paste box, combined with constant temperature and humidity chamber and homemade double-roll peeling tool, the solution is solved The problem of poor bonding in the prior art has achieved an effective evaluation of the strength of the white paper paste box and the fiber bonding strength.
Patent Information
- Application Number
- CN202311707204.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-12-13
AI Technical Summary
In the prior art, when detecting the firmness of the paste box bonding of white jam paper, there are double-sided adhesive relaxation, wrinkles and gaps, resulting in reduced adhesion, residual metal tool affects detection data, and inconsistent with the subsequent market use of the paste box process. question.
A white cardboard paste box bonding firmness test method is used, and the forward and reverse bonding test is carried out by cutting the test sample. A mold with rectangular holes and water-based adhesive is used. After applying glue, it is placed in a constant temperature and humidity chamber. The peeling effect was tested using a homemade double-roll peeling tool to evaluate the degree of fiber damage to judge the paper bond strength.
This method can effectively evaluate the strength of the paste box and the fiber bonding strength of the white cardboard, solve the problem of poor bonding, and is suitable for manual and roller coating, and can understand the differences in market adhesives and improve the accuracy and reliability of detection. .
Smart Images

Figure CN117705702B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of white cardboard subsequent processing and box pasting testing, and in particular to a method for testing the adhesion firmness of white cardboard box pasting. Background Art
[0002] Because the interlayer bonding strength index of white cardboard is highly valued by customers in the market, it plays a vital role in the subsequent processing and use, and is also related to the cost-effectiveness of the production process.
[0003] At present, the strength test of coated white cardboard uses an interlayer bonding instrument to understand the fiber bonding strength of white cardboard; the structure is shown in the attached figure of the specification Figure 1 As shown, the combination of double-sided tape b and sample c forms a sandwich structure, which is pressed between a metal flat anvil a and an aluminum block d; the inner surface of the upper part of the aluminum block a is hit by a pendulum, so that the aluminum block a is turned over and the sample c is destroyed in the Z direction. The energy absorbed by the sample during the destruction process is calculated by measuring the highest position of the swing. The existing technology has the following disadvantages:
[0004] 1. The adhesion of double-sided tape will be significantly loosened over time;
[0005] 2. Wrinkles and gaps on the double-sided tape will accelerate drying, resulting in reduced adhesion;
[0006] 3. Repeated use of metal flat anvils and aluminum blocks will cause residual adhesive on both sides to affect the test data;
[0007] 4. It is inconsistent with the box-pasting process used in the subsequent market. Therefore, a method for testing the adhesion firmness of white cardboard box-pasting is urgently needed. Summary of the invention
[0008] The purpose of the present invention is to provide a method for testing the adhesion firmness of white cardboard box pasting in view of the defects and shortcomings of the prior art, which can solve the technical problems in the prior art.
[0009] To achieve the above object, the technical solution adopted by the present invention is: comprising the following steps:
[0010] Step 1: Cut the paper into several test samples of the same size, distinguishing the vertical and horizontal directions, and place the test samples flat on a constant temperature parallel table to perform front and back adhesion tests;
[0011] Step 2: Use a prepared mold with the same size as the test sample and a thickness of 0.1 mm, with a 1 cm × 5 cm rectangular hole in the middle, and place it vertically on the cut test sample in the MD direction;
[0012] Step 3. Stir the test glue evenly, use a graduated dropper to take 0.1g and drop it on one end of the rectangular hole, then use a scraper to evenly apply the glue on one end of the rectangular hole mold on a sample with an area of 1cm×5cm to form a surface to be bonded; completely bond another sample to the surface to be bonded in the MD direction, and then use a heavy object to apply pressure on the bonding point to obtain several bonded samples, and the same amount of glue is used for each group of samples;
[0013] Step 4: Start timing the glued specimen in a constant temperature and humidity chamber and place it for 0.5h, 1h, and 2h respectively to test the drying of the glue at the bonding point at different times, determine the best performance of the glue, and then determine the paper bonding strength based on the best performance of the glue;
[0014] Step 5: After a certain period of rest, use a double-roller peeling tool to test the peeling effect;
[0015] Step 6: Take 5 groups of samples as one cycle. If the fiber damage after peeling off the bonding part is ≥50%, it is a qualified A-level product, and if it is less than 50%, it is an unqualified B-level product. For the test grade assessment of the test samples, please refer to the attached manual for details. Figure 4 .
[0016] 2. A method for testing the adhesion firmness of white cardboard box pasting according to claim 1, characterized in that: the double-roller peeling tool in step 5 comprises:
[0017] Brackets, there are two brackets, which are symmetrically fixed on both sides of the steel bottom tray;
[0018] Parallel steel rollers, there are two parallel steel rollers, and their ends are rotatably arranged on the brackets on both sides through bearings; the dimensions of the parallel steel rollers are 29 cm in length, 5 cm in end diameter, and 15.7 cm in circumference;
[0019] Spacing regulating valves, there are two spacing regulating valves, which are respectively connected to the ends of the parallel steel rollers through spacing adjusting chains;
[0020] Insert the test sample longitudinally between the parallel steel rollers so that the glue-bonded position of the test sample is placed at the intersection of the two roller surfaces. Then use tape to fix the remaining ends of the sample above the roller surface to the left and right parallel steel rollers respectively. Use the movement force of the bearings at both ends of the two rollers to rotate the roller surfaces in both directions at the same time to peel off the glue-bonded position.
[0021] As a further improvement of the present invention, the size of the test sample in step 1 is 10 cm×10 cm.
[0022] As a further improvement of the present invention, the glue in step 3 is a water-based adhesive, which has the appearance of a white to yellow emulsion, a solid content of 48%-52%, a viscosity of 7000-14000cps, a pH value of 7.0-8.5, and an ambient temperature of 10-30°C.
[0023] As a further improvement of the present invention, the heavy object in step 3 is a 1 kg weight, a rectangular plate is used to cover the adhesive surface of the test sample, and then a 1 kg weight is used to apply pressure for 30 seconds, using the uniformity of pressure applied by a flat object. In this experiment, the rectangular plate is a ruler.
[0024] As a further improvement of the present invention, the constant temperature and humidity chamber in step 4 is 23±1°C / 50±2%; and the standing time is 0.5-2h.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. Use the commonly used adhesives in the market to test the box-pasting samples. After a certain period of time, wait for the adhesive to dry and then tear the paper bonding part with a self-made double-roller peeling tool. According to the degree of fiber damage on the torn paper surface, evaluate the paper box-pasting strength and the fiber bonding strength of the white cardboard. Use this test method to determine whether the product will have the hidden danger of poor bonding after subsequent printing and processing;
[0027] 2. Use white cardboard to simulate subsequent bonding processing and determine the strength of white cardboard box pasting; use water-based adhesive, which is suitable for manual gluing and roller gluing. This can help understand the differences in market adhesives and solve customer complaints about weak bonding in subsequent use. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is a structural schematic diagram of the prior art.
[0030] Figure 2 It is a schematic diagram of the test sample gluing structure in the present invention.
[0031] Figure 3 It is a structural schematic diagram of the double-roller peeling tool of the present invention.
[0032] Figure 4 It is an experimental flow chart of the present invention.
[0033] Description of reference numerals:
[0034] Bracket g, steel bottom tray e, bearing h, parallel steel rollers f, spacing adjustment valve i, spacing adjustment chain j. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the accompanying drawings.
[0036] Embodiment 1:
[0037] This embodiment includes the following steps:
[0038] Step 1: Cut the samples into 10×10cm size, 5 sets of samples on the front and back, and place the samples vertically on a constant temperature flat table;
[0039] Step 2: Use a prepared mold with the same size as the sample and a thickness of 0.1 mm and a 1 cm × 5 cm rectangular hole in the middle, and fix it vertically on the cut sample in the MD direction;
[0040] Step 3: Stir the test glue evenly, use a graduated dropper to take 0.1g and drop it into one end of the rectangular hole, then use a scraper to evenly apply the glue into the rectangular hole to form a surface to be bonded; completely bond another sample to the surface to be bonded in the MD direction, cover the top of the test sample after glue application with a ruler and fix it, then use a 1Kg weight to apply pressure on the ruler, and apply pressure for 30s to obtain several glue-applied bonding samples, five in a group;
[0041] Step 4: After applying pressure for 30 seconds, the five glue test samples are placed in a constant temperature and humidity chamber for 0.5 hours;
[0042] Step 5. After standing for 0.5h (the sizing agent is 60% dry), use a homemade double-roller peeling tool to test the peeling effect. Insert a 10×10cm test sample longitudinally between the parallel double rollers, so that the test sample's glue bonding position is placed at the intersection of the double roller surfaces, and then use tape to fix the remaining ends of the sample above the roller surface to the left and right parallel double rollers respectively. Use the movement force of the bearings at both ends of the double rollers to rotate the roller surface in both directions at the same time to peel off the glue bonding part, and check the degree of damage to the fiber layer of the cardboard at the bonding part to determine the paper strength;
[0043] Step six, the above 5 groups of test samples were tested. The first group of fiber layer damage after peeling at the bonding place was 50%-80% strength (medium) of level 2, which was determined as qualified A-grade products; the second group of fiber layer damage after peeling at the bonding place was less than 50% strength (weak) of level 3, which was determined as unqualified B-grade products; the third group of fiber layer damage after peeling at the bonding place was less than 50% strength (weak) of level 3, which was determined as unqualified B-grade products; the fourth group of fiber layer damage after peeling at the bonding place was 50%-80% strength (medium) of level 2, which was determined as qualified A-grade products; the fifth group of fiber layer damage after peeling at the bonding place was less than 50% strength (weak) of level 3, which was determined as unqualified B-grade products. Combined with the above five groups of tests, it was determined to be an unqualified B-grade product.
[0044] Embodiment 2:
[0045] This embodiment includes the following steps:
[0046] A method for testing the bonding firmness of white cardboard comprises the following steps:
[0047] Step 1: Cut the samples into 10×10 cm size, 5 sets of samples on the front and back, and place the samples longitudinally on a constant temperature parallel table;
[0048] Step 2: Use a prepared mold with the same size as the sample and a thickness of 0.1 mm and a 1 cm × 5 cm rectangular hole in the middle, and fix it vertically on the cut sample in the MD direction;
[0049] Step 3: Stir the test glue evenly, use a graduated dropper to take 0.1g and drop it into one end of the rectangular hole, then use a scraper to evenly apply the glue into the rectangular hole to form a surface to be bonded; completely bond another sample to the surface to be bonded in the MD direction, cover the top of the test sample after glue application with a ruler and fix it, then use a 1Kg weight to apply pressure on the ruler, and apply pressure for 30s to obtain several glue-applied bonding samples, five in a group;
[0050] Step 4: After applying pressure for 30 seconds, the five glue test samples are placed in a constant temperature and humidity chamber for 1 hour;
[0051] Step 5. After standing for 1 hour (the glue application area is 80% dry), use a self-made double-roller peeling tool to test the peeling effect. Insert a 10×10 cm test sample longitudinally between the parallel double rollers, so that the glue application and bonding position of the test sample is placed at the intersection of the double roller surfaces. Then use tape to fix the remaining ends of the sample above the roller surface to the left and right parallel double rollers respectively. Use the movement force of the bearings at both ends of the double rollers to rotate the roller surface in both directions at the same time to peel off the glue application and bonded area, and check the degree of damage to the fiber layer of the cardboard at the bonding area to determine the paper strength;
[0052] Step 6. The above 5 groups of test samples were tested. The first group of fiber layers were damaged by 50%-80% strength (medium) after peeling off the bonding, which was level 2, and were determined to be qualified A-grade products; the second group of fiber layers were damaged by 50%-80% strength (medium) after peeling off the bonding, which was level 2, and were determined to be qualified A-grade products; the third group of fiber layers were damaged by 50%-80% strength (medium) after peeling off the bonding, which was level 2, and were determined to be qualified A-grade products; the fourth group of fiber layers were damaged by less than 50% strength (weak) after peeling off the bonding, which was level 3, and were determined to be unqualified B-grade products; the fifth group of fiber layers were damaged by 50%-80% strength (medium) after peeling off the bonding, which was level 2, and were determined to be qualified A-grade products. The above five groups of tests were combined to determine that they were qualified A-grade products.
[0053] Embodiment 3:
[0054] This embodiment includes the following steps:
[0055] A method for testing the bonding firmness of white cardboard comprises the following steps:
[0056] Step 1: Cut the samples into 10×10 cm size, 5 sets of samples on the front and back, and place the samples longitudinally on a constant temperature parallel table;
[0057] Step 2: Use a prepared mold with the same size as the sample and a thickness of 0.1 mm and a 1 cm × 5 cm rectangular hole in the middle, and fix it vertically on the cut sample MD direction sample (see Figure 4 )
[0058] Step 3: Stir the test glue evenly, use a graduated dropper to take 0.1g and drop it into one end of the rectangular hole, then use a scraper to evenly apply the glue into the rectangular hole to form a surface to be bonded; completely bond another sample to the surface to be bonded in the MD direction, cover the top of the test sample after glue application with a ruler and fix it, then use a 1Kg weight to apply pressure on the ruler, and apply pressure for 30s to obtain several glue-applied bonding samples, five in a group;
[0059] Step 4: After applying pressure for 30 seconds, the five glue test samples are placed in a constant temperature and humidity chamber for 2 hours;
[0060] Step 5. After standing for 2 hours (the glued area is completely dry), use a self-made double-roller peeling tool to test the peeling effect. Insert a 10×10 cm test sample longitudinally between the parallel double rollers, so that the glued bonding position of the test sample is placed at the intersection of the double roller surfaces. Then use tape to fix the remaining ends of the sample above the roller surface to the left and right parallel double rollers respectively. Use the movement force of the bearings at both ends of the double rollers to rotate the roller surface in both directions at the same time to peel off the glued bonding area, and check the degree of damage to the fiber layer of the cardboard at the bonding area to determine the paper strength;
[0061] Step six, the above 5 groups of test samples were tested. The first group of fiber layer damage after peeling of the bonding place was greater than 80% of the strength (strong), which was level 1, and was determined to be a qualified A-grade product; the second group of fiber layer damage after peeling of the bonding place was 50%-80% of the strength (medium), which was level 2, and was determined to be a qualified A-grade product; the third group of fiber layer damage after peeling of the bonding place was greater than 80% of the strength (strong), which was level 1, and was determined to be a qualified A-grade product; the fourth group of fiber layer damage after peeling of the bonding place was greater than 80% of the strength (strong), which was level 1, and was determined to be a qualified A-grade product; the fifth group of fiber layer damage after peeling of the bonding place was greater than 80% of the strength (strong), which was level 1, and was determined to be a qualified A-grade product. Combined with the above five groups of tests, it was determined to be a qualified A-grade product.
[0062] After adopting the above method, the beneficial effects of this specific implementation are:
[0063] 1. Use the commonly used adhesives in the market to test the box-pasting samples. After a certain period of time, wait for the adhesive to dry and then tear the paper bonding part with a self-made double-roller peeling tool. According to the degree of fiber damage on the torn paper surface, evaluate the paper box-pasting strength and the fiber bonding strength of the white cardboard. Use this test method to determine whether the product will have the hidden danger of poor bonding after subsequent printing and processing;
[0064] 2. Use white cardboard to simulate subsequent bonding processing and determine the strength of white cardboard box pasting; use water-based adhesive, which is suitable for manual gluing and roller gluing. This can help understand the differences in market adhesives and solve customer complaints about weak bonding in subsequent use.
[0065] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in this field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for testing the adhesion firmness of white cardboard pasting boxes, characterized in that: The following steps are involved: Step (1), cutting the paper into a number of test samples of equal size, distinguishing between the vertical and horizontal directions, placing the test samples flat on a constant temperature parallel table, and conducting a front and back adhesion test; Step (2), using a prepared mold of the same size as the test sample and with a thickness of 0.1 mm and a 1 cm × 5 cm rectangular hole in the middle, vertically placed on the cut test sample in the MD direction; Step (3), stir the test glue evenly, use a graduated dropper to take 0.1g and drop it onto one end of the rectangular hole, then use a scraper to evenly apply the glue at one end of the rectangular hole mold to a sample with an area of 1cm×5cm to form a surface to be bonded; another sample is completely bonded to the surface to be bonded in the MD direction, and then a heavy object is used to apply pressure at the bonding point, thereby obtaining several bonded samples, and the same amount of glue is used for each group of samples; Step (4), start timing the glue-bonded sample in a constant temperature and humidity chamber, and let it stand for 0.5 h, 1 h, and 2 h, respectively, to test the drying of the glue at the bonding point at different times, determine the best performance of the glue, and then determine the paper bonding strength based on the best performance of the glue; Step (5), after a certain period of standing, use a double-roller peeling tool to test the peeling effect; the double-roller peeling tool includes: Brackets (g), there are two brackets (g), which are symmetrically fixed on both sides of the steel bottom tray (e); Parallel steel rollers (f), wherein there are two parallel steel rollers (f), and the ends of the parallel steel rollers (f) are rotatably arranged on brackets (g) on both sides through bearings (h); The dimensions of the parallel steel roller (f) are 29 cm in length, 5 cm in end diameter, and 15.7 cm in circumference; Spacing regulating valves (i), wherein there are two spacing regulating valves (i), and each of the spacing regulating valves (i) is connected to the end of the parallel steel roller (f) via a spacing adjusting chain (j); Insert the test sample longitudinally between the parallel steel rollers (f), so that the test sample's adhesive bonding position is placed at the intersection of the two roller surfaces, and then use adhesive tape to fix the remaining ends of the sample above the roller surface to the left and right parallel steel rollers (f), and use the movement force of the bearings at both ends of the two rollers to rotate the roller surfaces in both directions at the same time to peel off the adhesive bonding part; Step (6): Test 5 groups of samples as one cycle. If the fiber damage after peeling off the bonding part is ≥50%, it is a qualified A-grade product, and if the fiber damage is less than 50%, it is an unqualified B-grade product.
2. A method for testing the adhesion firmness of white cardboard box pasting according to claim 1, characterized in that: The size of the test sample in step (1) is 10 cm×10 cm.
3. A method for testing the adhesion firmness of white cardboard box pasting according to claim 1, characterized in that: The glue in step (3) is a water-based adhesive, which has the appearance of a white to yellow emulsion, a solid content of 48%-52%, a viscosity of 7000-14000 cps, a pH value of 7.0-8.5, and an ambient temperature of 10-30°C.
4. A method for testing the adhesion firmness of white cardboard box pasting according to claim 1, characterized in that: The weight in step (3) is a 1 kg weight. A rectangular plate is used to cover the adhesive surface of the test sample, and then a 1 kg weight is used to apply pressure for 30 seconds. The uniformity of pressure applied by a flat object is used. In this experiment, the rectangular plate is a ruler.
5. A method for testing the adhesion firmness of white cardboard box pasting according to claim 1, characterized in that: The constant temperature and humidity chamber in step (4) is 23±1°C / 50±2%; the standing time is 0.5-2h.
Citation Information
Patent Citations
Platen tape test method and device
CA2805577A1
Adhesive strength meter for corrugated board
CN102323210A